PENGALAMAN PERSALINAN IBU DI RUMAH SAKIT PUSRI PALEMBANG - Nainggolan, Sutrisari Sabrina (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Every day there are around eight hundred thirty thousand mothers in the world die from diseases/complications related to pregnancy and childbirth. The cause of maternal death can be due to maternal factors or factors from the fetus. Labor is a very important event in a woman's life. The experience that they feel while undergoing labor is certainly different. When a woman has the experience of the first child with normal labor, there will be happiness and also a feeling of fear related to the condition of the fetus. Unlike the case when the woman gives birth to her second child by cesarean, there will be a feeling of worry, anxiety and fear. This feeling arises because the woman will experience a labor condition that is different from the previous labor. Qualitative study of phenomenology to explore the experience of labor. Six participants, namely multigravida mothers, had experiences of normal labor and sectio, were willing to be participants, were able to express their labor experiences, and were in place when the study was conducted. Data was collected through in-depth interviews twice which were completed with field notes. Interviews were recorded and then transcripts of interviews were made and analyzed using the Collaizi approach. The results of the study revealed three themes, namely the response at delivery, coping mechanism at delivery, and support obtained when facing labor. For nursing services, there needs to be an explanation for patients and families related to labor. This is important to reduce client and family anxiety. In addition, the results of this study can be used as information in improving health services not only from the biological side but on the psychological aspect of the mother.Keywords : Experience, Childbirth